Two isoforms of aquaporin 2 responsive to hypertonic stress in bottlenose dolphin - Suzuki, Miwa; Wakui, Hitomi; Itou, Takuya; Segawa, Takao; Inoshima, Yasuo; Maeda, Ken; Kikuchi, Kiyoshi (Journal of experimental biology, 2016)
This study investigated the expression of aquaporin 2 (AQP2) and its newly found alternatively spliced isoform (alternative AQP2) and the functions of these AQP2 isoforms in the cellular hyperosmotic tolerance in the bottlenose dolphin Tursiops truncatus. mRNA sequencing revealed that alternative AQP2 lacks the fourth exon and instead has a longer third exon that includes a part of the original third intron. The portion of the third intron, now part of the coding region of alternative AQP2, is highly conserved among many species of the order Cetacea but not among terrestrial mammals. Semi-quantitative polymerase chain reaction revealed that AQP2 was expressed only in the kidney, similar to terrestrial mammals. In contrast, alternative AQP2 was expressed in all organs examined, with strong expression in the kidney. In cultured renal cells, expression of both AQP2 isoforms was upregulated by the addition to the medium of NaCl but not by the addition of mannitol, indicating that the expression of both isoforms is induced by hypersalimity but not hypertonicity conditions. Treatment with small interfering RNA for both isoforms, resulted in a decrease in cell viability in hypertonic medium (500 mOsm/kg) when compared to controls. These findings indicate that the expression of alternatively spliced AQP2 is ubiquitous in cetacean species and it may be one of the molecules important for cellular osmotic tolerance throughout the body.